Latent profile analysis of fear of progression in obstructive sleep apnea hypoventilation syndrome patients: a cross-sectional study - Yuanhui Ge; Dongfang Ge; Zhengxiang Guo; Yuecong Wang; Xin Wang; Cuilan Wang (BMC Psychology)
Abstract Objective This study aims to identify distinct subtypes of Fear of Progression (FOP) in patients with Obstructive Sleep Apnea-Hypopnea Syndrome (OSAHS) using latent profile analysis and to investigate associated demographic factors to facilitate personalized treatment by healthcare professionals, thereby improving clinical symptoms and treatment outcomes in OSAHS patients. Methods This study employed a convenience sampling method to recruit 307 patients with OSAHS. A cross-sectional survey was conducted to collect data on patients' demographics, the Fear of Progression Questionnaire-Short Form, the Social Support Rating Scale, and the Health Promoting Lifestyle Profile II. Latent profile analysis was used to investigate the heterogeneity of FOP in this patient sample. Results FOP in patients with OSAHS can be categorized into three latent subtypes: low FOP group(16.6%), moderate FOP group (44.3%), and high FOP group (39.1%). Univariate analyses revealed that gender, education level, smoking history, exercise frequency, coexistence of other chronic illnesses, sleeping posture, OSAHS diagnosis, social support, and health-promoting behaviors significantly influenced the level of FOP. Multivariate logistic regression analysis further revealed that the risk of moderate to high fear of disease progression was associated with lower social support, reduced engagement in health-promoting behaviors, sleep positions (e.g., sleeping on one’s side), occasional smoking, and the diagnostic severity of OSAHS. Conclusions This study describes the characteristics of different FOP subtypes, which aids healthcare professionals in gaining a deeper understanding of the population heterogeneity of FOP status in patients with OSAHS. Consequently, it facilitates the development of more precise health promotion intervention strategies, and actively responds to the implementation of "Healthy China 2030".